Interaction of low density lipoproteins with arterial proteoglycans The role of charge and sialic acid content - Camejo, Germán; López, Aura; López, Flor; Quiñones, Jorge (Atherosclerosis, 1985)
The interaction of low density lipoproteins (LDL) with chondroitin sulfate-rich arterial proteoglycans appears to be initiated by coulombic interactions that lead to insoluble complexes. Once formed, large LDL aggregates are held together by non-polar associations. The irreversible formation of LDL proteoglycans aggregates was evaluated for different LDL preparations by definition of an avidity coefficient (A r) using a Langmuir isotherm. LDL from different subjects, when tested against the same lipoprotein-complexing proteoglycan (LCP), gave A r values ranging from 1−9 × 10 6 L M . High avidity values were associated to lipoproteins with apparent isoelectric points above 6.5. These lipoproteins show low Sialic acids content. The content of N-acetyl and N-acetyl,O-acetyl Sialic acid was found inversely correlated with the avidity coefficient for the arterial LCP. Reductions of 42% on the LDL sialic acid content, by neuraminidase treatment, induced a 10-fold increment in their avidity for the lipoprotein complexing proteoglycan. The results indicate that at low ionic strength and physiological Ca 2+-concentration and pH, the surface charge of LDL is an important modulator of the interaction with the arterial proteoglycan. Sialic acid, perhaps because of its exposure at the LDL surface, plays a determinant role in the in vitro association of LDL with the polyanionic proteoglycans. It is possible that in the intima-media the sialic residues of LDL and its balance of surface charges will control part of the interactions with the proteoglycans of the extracellular matrix.